Povysenie rabotosposobenosti i urovnja sportivnych dostizenij u begunov na srednie i dlinnye distancii pod vlijaniem priema preparata "Gipoksen" - Volkov, N. I.; Igumenova, L. A. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The activation of free radical oxidation in conditions of the intense muscular activity is accompanied by infringements of processes of the tissue breath that is the reason of fast developing exhaustions and the reduce of the bearableness of hypoxia conditions, permanently arising during the performance of the exercise. The application of the preparations having antioxidizing and antihypoxia actions, conducts to the destruction of the oxidation products, stabilizes the work of the respiratory enzymes located on mitochondrion membranes, and reduces the speed of the development of exhaustion during work. The preparation "Hypoxen" with such action was synthesized in the scientific research institute of pure biological products, Saint Petersburg. The present research was is undertaken with the purpose of the studying of influence of the preparation on biopower functions and the serviceability of the athletes specializing in running on average and long distances. The laboratory and field tests have shown the high efficiency and the specificity of the protective action of the preparation at the intense muscular work.